A comparison of personality traits and behavioral characteristics between patients with alcohol dependence and common mental disorders according to sex - a controlled study - Demirbaş, Hatice; Özgür İlhan, İnci; Arslan, Ecmel; Şentürk, Vesile; Yücel, Onur (Journal of Dependence, 2010)
Objective: Över the last decades, prevalence of alcohol dependence has increased in both males and females and has seen gender differences in clinic. In this study, it is aimed to determine personality traits and behavioural characteristics between patients with alcohol dependent men and women compared to common psychiatric disorders.Methods: The sample consisted of 72 inpatients from the Department of Psychiatry of Ankara University between October 2005 and June 2007. Eighteen females with alcohol dependence were enrolled along with an equal number of alcohol dependent males in the same period. Control group consisted of male and female inpatients with common mental disorders in the same period. The Minnesota Multiphasic Personality Inventory (MMPI) was administered to all subjects. Data was analysed using one-way anova and Tukey HSD.Results: There was a statistical differences between means of MMPI subtests in patients groups (F=172.796, p=0.009). "Psychopathic deviation” was significantly higher in alcohol dependent female patients than alcohol dependent male patients, female and male patients with common mental disorders (P=.005). MMPI profiles similar were across the two psychopathological groups for both males and females, except for the "psychopathic deviation" outcome measure.Conclusion: Our findings point that alcohol dependent females, are different from patients with alcohol dependent males and common mental disorders according to psychopathic tendency. This different personality traits and behavioural patterns are important to recognize differences, plan efficient treatment programs and estimate relaps.
Keywords: Gender; alcohol dependency; The Minnesota Multiphasic Personality Inventory (MMPI); personality; psychiatric patient